Implementasi Metode Inquiry untuk Meningkatkan Hasil Belajar Peserta Didik - Alya Fadiyah Effendi; Sukardi Sukardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
The quality of education in Indonesia is fairly low which is at the bottom of 12 countries in Asia. on the results of observations made in class X TITL at SMK Negeri 5 Padang more than half of the students have not reached the Learning Objective Achievement Criteria (KKTP) which is set at large equal to 75. Government efforts to overcome the low quality of education in Indonesia by issuing policies and improvements with educator certification, equal distribution of education personnel, curriculum improvement, school operational assistance funds, and adoption of new concepts. The prototype curriculum launched by the Minister of Education and Culture and Research Nadiem Makarim is designed as a more flexible curriculum framework centered on basic materials and supporting the unique characteristics and abilities of students. Adaptation of new concepts with inquiry methods that involve students in the learning process, with this method it is expected that students can be more active and can solve problems independently which ultimately can develop students' social attitudes. This research is limited to the implementation of the Inquiry method in the subject of basic electrical engineering element 6 regarding the basic theory of electricity and materials used in electricity.This study aims to determine the implementation of the inquiry method to improve student learning outcomes in the basic subjects of basic electricity engineering class X TITL at SMK Negeri 5 Padang. This research is a quantitative study with the Pre-Experiment Design method of The One Group Pretest Posttest type. The subjects in this study were students of class X TITL 1 SMKN 5 Padang. The research instrument used is a pretest and posttest question in objective form. The results of the effect size of students of 0.69 are in the medium category and classical completeness of 88%.